Study on Parametric Analysis of Piled Raft Foundation System Using Finite Element Approach - Niraula, Santosh; Acharya, Indra Prasad (Journal of Advanced College of Engineering and Management, 2021)
To accommodate the shear requirement and settlement requirement of high rise construction, the concept of piled-raft foundation has been developed. This research deals with successive analysis of parameters of piled-raft foundation system using PLAXIS-2D as a FEM tool. Plain strain analysis of piled raft foundation system has been conducted out by successive fixing up of parameters. For the analysis two cases has been studied for piled-raft lying on silty soil deposit and on clayey deposit with respect to uniform static loading from superstructure. The result of successive variation of parameters showed that variation has limiting effect on stress and displacement behavior. The analysis is also performed for raft of different relative stiffness and pile of different relative compressibility and load sharing between plain strain pile and raft has been analyzed.